Exploring the Substantial Role of Multiplex Pcr to Diagnose Malaria in Eastern Nepal - Bhattarai, Narayan Raj; Rai, Keshav; Rijal, Suman; Ghimire, Anup; Khanal, Basudha (Journal of Chitwan Medical College, 2019)
Background: Malaria is still a major health problem in Nepal as 43.3% of population are at risk of infection. However, the national priorities have been given to achieve malaria elimination in Nepal, the question of diagnostic accuracy could jeopardize the elimination target. Among others, multiplex PCR could be the reliable alternative tool to detect the low number of parasitemia and circulating asymptomatic infection in low endemic countries like Nepal. Hence, this paper aims to analyse the diagnostic precision among microscopy, rapid diagnostic test (RDT) and multiplex real time PCR assay. Methods: A total of 63 archived blood samples obtained from patient with clinical suspicion of malaria were subjected to multiplex PCR and their results were compared with microscopy and rapid diagnostic test. The Latent Class Analysis (LCA) approach was used to compare the diagnostic precision among three different assays. Results: Our study documented that PCR had 97.4% sensitivity and 83.9% specificity. Among the negative microscopy results, 10 (15.9%) were false negatives whereas 4 (6.3%) RDT results were false negatives based on PCR results. Conclusions: PCR could be the useful alternative tool to detect the low number of parasite in low endemic settings which could be crucial to rule out the false diagnosis determined by microscopy or RDT.